How Does Technology Support The Control Of Non-Communicable Diseases? A Digital-Based Community Health Worker Empowerment Intervention - Muhammad Revi Purnomosidi; Wahyu Hanifah Mutmainah; Septiana Nur Haliza; Elvaretta Ramadhani Putri D; Elvina Friska Rindani; Etiya Mulya Ningsih; Salwa Alawiyah (Journal Of Humanities Community Empowerment, 2025)
Hypertension and diabetes are the leading causes of high morbidity and mortality, particularly in rural areas with limited access to healthcare services and low awareness of disease prevention. The PRIMA HEALTH program was developed to manage non-communicable diseases comprehensively through preventive, curative, and rehabilitative approaches, with a focus on empowering village health cadres and encouraging active community participation. The program combines cadre training with the use of the digital platform e-SEHAT for continuous health data recording, monitoring, and analysis. This system enables systematic documentation of blood pressure, blood glucose levels, and community health activities, providing a data-driven basis for decision-making at the community level. During five months of implementation, PRIMA HEALTH improved cadres’ ability to operate digital tools and coordinate routine health checks, with community participation reaching 80%. The digital system contributed to a 40% reduction in uncontrolled hypertension and diabetes cases and promoted adherence to physical activity and healthy eating. The findings indicate that the PRIMA HEALTH program effectively strengthens community-based health monitoring systems, enhances intervention responsiveness, and supports the sustainable management of non-communicable diseases